"How may i help you?" Says a robot: Examining language styles in the service encounter. (September 2019) - Choi, Sungwoo; Liu, Stephanie Q.; Mattila, Anna S.
Highlights: Consumers respond more favorably to human service agents who use literal (vs. figurative) language. The language style effects extend to service robots, but not to service kiosks based on the notion of anthropomorphism. Perceived credibility is the psychological mechanism explaining the impact of language styles on service encounter satisfaction. Hospitality managers should encourage frontline employees to use literal (vs. figurative) language when interacting with customers. Furthermore, firms can enhance service encounter quality by tuning their service robots to use literal language, while flexibility in language styles is fine for service kiosks. Abstract: Is figurative or literal language more effective in the service encounter context? The current research reveals that literal language used by a service provider might be more congruent with conversational norms, thus leading to better customer evaluation. Most importantly, the effectiveness of language styles (literal vs. figurative) is contingent on a service agent type (human vs. robot vs. kiosk). Specifically, consumers respond more favorably to human service agents who use literal (vs. figurative) language, and due to the notion of anthropomorphism such an effect extends to service robots. However, the language style effect is not observed among service kiosks as they lack humanlike features. Furthermore, perceived credibility is the underlying mechanism explaining the language style effect among service agents.